Penerapan PSAK 50 dan PSAK 55 pada Bank X Surabaya - Pikir, Toto Warsoko (Widya Mandala Surabaya Catholic University, 2012)
Implementation of SFAS 50-55 especially concerning Allowance for Impairment Losses (CKPN) or long referred to the Establishment of Asset Allocation (PPA) for banking takes quite a long time. Banks were given a chance until the end of 2011 to complete the calculation that will be used at the beginning of 2012. In fact in turns out that the application CKPN compared with PPA penelitian apparently based on Bank X in Surabaya produce significant computation when compared to the old system. December 31, 2011 for the position of getting a difference of Rp 1.389 million, or in other words the amount of load reduced. However, in accordance with Bank Indonesia for the calculation of Core Capital Bank would still be required to wear a PPA calculations.